PROPOSED SOLUTION TO IMPROVE SINGLE IDENTITY SYSTEM (SID) AND BEGEMS AUTO TRACKING SYSTEM (BEATS) USING SIX SIGMA FRAMEWORK IN COAL MINING INDUSTRY - A CASE STUDY IN PT. BERAU COAL - Djali, Febriwiadi
PT Berau Coal is a subsidiary of the Sinarmas Mining Group which is engaged in coal mining in Berau Regency, East Kalimantan. In its operational activities, one of the aspects that must be managed is safety. PT Berau Coal has built a Single Identity System (SID) and BeGeMS Auto Tracking System (BEATS) as a program to improve mining safety performance. The purpose of this research is to answer how to increase the use of SID and BEATS in mining safety management. The author use Six Sigma with a DMAIC framework (Define, Measure, Analyze, Improve and Control). At the Define stage, identification of opportunities for improvement, the process of implementing hazard reports, inspection and observation, as well as the scope of this research were carried out. The Measure stage consists of what aspects are being measured, the measurement system and data collection. In the Analyze stage, all data that has been collected is analyzed to find the root of the problem using Five Why. The root of the problem is the absence of reward and punishment for workers for using BEATS in carrying out hazard reports, inspections and observations using BEATS and the absence of notification features in the current BEATS application. Alternative solutions are delivered at the Improve stage by referring to the foundation of safety which includes people, process and technology by developing gamification, integrated working permits and notifications features that are integrated with SID and BEATS. In the Control stage, verification and documentation of the results are carried out according to the time specified and evaluated whether the results of the improvements have met the key success factors, namely employee adoption and ontime follow-up using BEATS reaching 95% and hazard reporting, inspection, observation and closing follow-up with BEATS reaching 100 %. The development of gamification, integration of working permits and notifications features will be carried out by third parties with a process of mapping needs, creating mechanisms for each feature, developing information systems, testing by users, implementing, monitoring and evaluating. All of these stages will be completed in the 26th week of 2021.